Postnatal perineal problems. Issue 7 (July 2016) - Field, Alexander; Mistry, Megha; Field, Elizabeth
The majority of the women in the UK who deliver a baby vaginally sustain perineal trauma that requires suturing. GPs are frequently consulted by women regarding perineal health after delivery, either with specific concerns or opportunistically at the 6–8 week routine postnatal check. The aim of this article is to explore the common presentations and underlying pathologies of postpartum perineal problems, their management in primary care and when to refer. We also aim to emphasise the need for a holistic approach and to consider where perineal problems fit into the broader picture of postnatal health.